Masters of sociological thought; : ideas in historical and social context - Coser, Lewis A., 1913- (Rawat, 1996)
It deals with the more recent developments in sociological theory as well as with the master theorists. The final chapter provides a discussion of the major theoretical orientations that have emerged between the 1940's and the 1960's